Let's go through each question one by one.
Question 1: The expression \( 5^{-\sqrt{3}} \) can be rewritten using the rule of rational exponents. The negative exponent indicates a reciprocal, and the square root can be expressed as an exponent of \( \frac{1}{2} \). Thus:
\[ -\sqrt{3} = -3^{\frac{1}{2}} = -\frac{3}{2} \]
So the rational exponent is:
The rational exponent is \(-\frac{3}{2}\).
Question 2: For \( \frac{3\sqrt{8}}{\sqrt{2}} \), we can rewrite it using exponents:
\[ 3\sqrt{8} = 3 \cdot 8^{\frac{1}{2}} = 3 \cdot (2^3)^{\frac{1}{2}} = 3 \cdot 2^{\frac{3}{2}} \] \[ \sqrt{2} = 2^{\frac{1}{2}} \]
Now substituting these into the expression:
\[ \frac{3 \cdot 2^{\frac{3}{2}}}{2^{\frac{1}{2}}} = 3 \cdot 2^{\frac{3}{2} - \frac{1}{2}} = 3 \cdot 2^{\frac{2}{2}} = 3 \cdot 2^1 = 3 \cdot 2 = 6 \]
Thus:
\( 3\sqrt{8}/\sqrt{2} = 6 \).
Question 3: For \( \frac{49\sqrt{}}{7^{-3}} \), we first rewrite \( 49 \) and the exponent properties:
- Note that \( 49 = 7^2 \).
- Thus, we can write:
\[ \frac{49}{7^{-3}} = \frac{7^2}{7^{-3}} = 7^{2 - (-3)} = 7^{2 + 3} = 7^5 \]
The rational exponent in the new expression \( 7^5 \) is simply:
The rational exponent for the new expression is \( 5 \).
Question 4: To determine if \( 4^3 \cdot (3\sqrt{64})^2 = 4^6 \) is true or false:
- First, calculate \( (3\sqrt{64})^2 \): \[ 3\sqrt{64} = 3 \cdot 8 = 24 \Rightarrow (24)^2 = 576 \]
Now, calculate \( 4^3 \) and \( 4^6 \):
- \( 4^3 = 64 \), and \( 4^6 = 4096 \).
Now, check the equation: \[ 64 \cdot 576 \neq 4096 \]
So the equation is False.
Question 5: For the equation \( (\sqrt{25})^4 \cdot 5^6 = 5^8 \):
First, calculate \( \sqrt{25} \):
- \( \sqrt{25} = 5 \).
Now, evaluating \( (\sqrt{25})^4 \): \[ (5)^4 = 625, ; 5^6 = 15625. \]
Now check: \[ 625 \cdot 15625 \neq 5^8 (which equals 390625). \]
Now, notice:
- \( (5)^4 \cdot (5)^6 = (5)^{4+6} = 5^{10} \), which is not equal to \( 5^8 \).
So the equation is False.
To summarize:
- Question 1: \(-\frac{3}{2}\)
- Question 2: \(6\)
- Question 3: \(5\)
- Question 4: False
- Question 5: False